The relationship between school personnel's confidence with using the school‐wide positive behaviour intervention support model and its sustainability. Issue 3 (14th December 2018) - Chitiyo, Jonathan; May, Michael E.; Mathende, Allen M.; Dzenga, Chaidamoyo G.
Abstract : Evidence demonstrating the effectiveness of the School‐wide Positive Behaviour Intervention Support model (SWPBIS) in managing problem behaviour among school students has been widely disseminated. As a result, the SWPBIS model is now widely implemented in schools across the US. Despite its widespread implementation and evidence demonstrating its efficacy, little is known about its sustainability. The scarcity of research studies examining the factors that influence the sustainability of SWPBIS provides a strong rationale for this study. The purpose of this study was to explore the relationship between school personnel's confidence with using SWPBIS and its sustainability. Participants were 104 school personnel employed in schools that implement SWPBIS in a southern region of Illinois. Regression analyses revealed that there is a significant relationship between personnel's confidence with using the model and its sustainability. The results led to important implications for practitioners involved in the implementation of SWPBIS and directions for future research are provided.